Optimizing Legal Protection against Gender-Based Violence From an Islamic Perspective - Saniah, Nur; Marlina, Marlina; Damanik, Lia Agustina (Institut Agama Islam Negeri Kendari, 2024)
Gender-based violence in Indonesia is increasingly concerning, despite the existence of numerous laws and regulations aimed at its regulation. This violence significantly impedes development, as its multifaceted impact hinders women's participation, compromises health, and diminishes autonomy across political, economic, social, and cultural spheres. The research addresses several key questions: 1) What is the extent of legal protection against gender-based violence in Indonesia? 2) How is gender-based violence addressed within Islam? 3) How can legal protection against gender-based violence be optimized from an Islamic perspective? The research methodology is qualitative, using a normative approach and drawing from secondary sources like literature accessed through library research. Data analysis is conducted through descriptive analysis techniques. The findings of the research indicate that in Indonesia, legal protection against gender-based violence is addressed through various regulations, and similarly, within Islam, there have been numerous reforms pertaining to gender-based protection found in the Quran and hadith. Strategies like theological education, moral guidance, gender equality promotion, and family development with a gender perspective can enhance legal protection against gender-based violence in line with Islamic principles. Aligned with these findings, the article emphasizes the vital importance of preventive measures to reduce the rise of gender-based violence.